Preventing Corruption in Indonesia: The Urgent Need for Political Education - Widodo, Sudiyo; Suwartini, Sri; Absori; Fitriciada Azhari, Aidul (Universitas Pendidikan Ganesha, 2025)
Corruption remains a serious threat to democracy and governance. High voter turnout does not automatically reflect substantive democracy, as many citizens still have limited political understanding, resulting in suboptimal awareness of their rights, obligations, and oversight role. This study aims to analyze the role of political education as a strategic instrument in preventing corruption by instilling the values of integrity, transparency, and accountability, while strengthening public participation in policy oversight. This research employed a sociological-normative legal approach that combined statutory and doctrinal analysis (das sollen) with empirical observation of legal practices and public responses (das sein). The subjects of this study included statutory documents, legal literature, policy reports, law enforcement perspectives, and community experiences related to anti-corruption efforts. Data were collected through literature review, interviews with selected respondents, field observations, and documentation, then analyzed qualitatively using descriptive and thematic approaches. The findings reveal that political education contributes to increasing legal awareness, fostering anti-corruption values, creating critical voters, and encouraging public oversight of governance. However, its current implementation remains minimal and fragmented, often limited to supplementary material in schools and incidental public campaigns. This study concludes that political education needs to be developed systematically to build an anti-corruption culture and strengthen democracy, involving collaboration between the government, political parties, and educational institutions in curricula and public programs.